Pengembangan Strategi Industri Pengolahan Ikan PT. Palu Jaya Utama Kecamatan Palu Utara Kota Palu Sulawesi Tengah - Tulak, Alber (AGROTEKBIS, 2013)
The aims of study to analyze the development strategy of the fish industry processing PT. Palu Jaya Utama, in  Palu of Central Sulawesi with identifying internal and external factor. The determination of respondents in (purposive) amounted from internal factor on the part of 2 person, they are internal manager and external corporate and the labor amounted to a person from department of Marine and Fisheries. The achievement of the purpose of the study was conducted by using qualitative descriptive analysis and SWOT analysis PT. Palu Jaya Utama is a fishery processing industries such as tuna, cakalang, deho, ruma-ruma, lajang, katombo and bandeng by non loin and loin frozen then marketed to Jakarta and Bali.  Based onthe results ofthe SWOT analysis showed that the fish processing industry PT. Palu Jaya Utamais at first kwadaran (aggressive), then the company can use the SO strategy in whicha company may maximize its strength the are magnitude of production, skilled labor, excellent products, fishing fleet, and a strategic location to enjoy the chances are availability of market, human resources, government support, technology, and fish resources to improve and expand the marketing of product sthrough government programs.